LB009 Motor neuroprosthesis to restore motor control for the command of digital devices: an early feasibility study of safety in subjects with severe quadriparesis. (26th July 2022) - Majidi, S; Fry, A; Harel, N; Escalon, M; Breyman, E; Weber, D; Putrino, D
Abstract : Background: Brain-computer interfaces (BCIs), functioning as motor neuroprostheses, have the potential to restore the transmission of neural signal from the cerebral cortex to control digital devices and improve functional independence in patients with severe paralysis. Methods: COMMAND is an FDA-approved, NIH-funded single arm, open-label, prospective early feasibility study designed to enroll 6 patients with severe quadriparesis to receive an endovascular implantable motor neuroprosthesis (Stentrode, Synchron Inc, Brooklyn, NY). The primary outcome measures include treatment related serious adverse events within 12-month after device implantation. Secondary outcome measures include restoration of neural signal from the cerebral cortex utilized for neuromuscular control of digital devices, resulting in the successful execution of non-mechanical digital commands, e.g., for the control of personal computers. The study device comprises of three parts: 1) Endovascular electrode array and lead (Stentrode™), implanted percutaneously via the jugular vein in the superior sagittal sinus adjacent to the motor cortex using endovascular approach; 2) Implantable Receiver Transmitter Unit (IRTU) implanted in the pectoral region; and 3) Controller, including an External Receiver Transmitter Unit (ERTU), Signal Control Unit (SCU) and Software Application. Results: A 67 year-old patient with complete quadriplegia from amyotrophic lateral sclerosis (ALS) enrolled into the study and completed a screening process which included CTV and MRV to ascertain normal venous sinus anatomy, with two patent jugular veins and bilateral patent transverse sinuses. Using a right internal jugular vein access, the investigational endovascular Stentrode BCI was implanted in the superior sagittal sinus adjacent to primary motor cortex. Co-registration to enable accurate anatomical targeting was achieved by fusing structural MRI data with intra-procedurally acquired 3D-volume (3D-DSA). A sub-clavicular subcutaneous pocket was created to place the IRTU. Then, the lead was tunneled to the pocket and connected to the IRTU. Before closure of the wound, impedance measurement was taken which confirmed functionality of the system. The patient tolerated the procedure very well, was successfully extubated after the procedure and remained neurologically at his baseline. Of note, the patient was started on dual antiplatelet therapy 2 weeks prior to the surgery and will be continued on this regimen for 3 months. The participant will undergo machine-learning-assisted training to use wirelessly transmitted electrocorticography signals associated with attempted movements to control multiple mouse-click actions, including zoom and left-click. Used in combination with an eye-tracker for cursor navigation, the patient will practice controlling a computer to conduct instrumental activities of daily living (IADL) tasks. Conclusion: We describe the first US in-human experience of a minimally invasive, fully implanted, wireless motor neuroprosthesis using an endovascular stent-electrode array to transmit electrocorticography signals from the motor cortex for multiple command control of digital devices. Disclosures: S. Majidi: None. A. Fry: None. N. Harel: None. M. Escalon: None. E. Breyman: None. D. Weber: None. D. Putrino: None.